Tingkat Kecemasan Guru Taman Kanak-Kanak Dalam Pembelajaran Jarak Jauh Di Kota Tasikmalaya - Zulfa Azkiya; Elfan Fanhas Fatwa Khomaeny; Fajar Nugraha (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
Learning during the COVID-19 pandemic was turned into distance learning. In this COVID-19 pandemic situation, the learning process does not run as usual, with this situation causing anxiety for teachers in general. This study aims to determine the level of anxiety of Kindergarten teachers in Distance Learning in Tasikmalaya City. Therefore, to determine the level of teacher anxiety, a research was conducted using descriptive quantitative research methods through distributing questionnaires based on the anxiety theory of Robert L Spitzer which consisted of 7 instruments (GAD-7). The population in this study amounted to 407 teachers, and the number of samples in this study amounted to 202 teachers. This research uses google form. The results of the study of 218 people showed that the level of anxiety of kindergarten teachers in PJJ in Tasikmalaya City was in the category of moderate anxiety with a percentage value of 47.2%, with the difference in anxiety levels in the category of not having anxiety was 3.2%, while the difference in anxiety levels in the category of not having anxiety was 3.2%. the low category is 11.9% and the difference in the high level of anxiety category is 37.6%. Keywords: Anxiety, Kindergarten, Distance Learning References Afiani Rara. (2020).“Inovasi Teknologi Dalam Pembelajaran Pada Masa Pandemic Covid-19 Di MI Nurul Yaqin, Al Amin, M. N. K. (2020). Menakar Nilai Kemanfaatan dari Penangguhan Walimat Al- ‘Ursy Di Masa Darurat COVID-19 Melalui Sadd Adz-Dzari’ah. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 27–38. Allen, Jennifer L., and Rebecca Lerman. (2018). "Teacher Responses to Anxiety in Children Questionnaire (TRAC): psychometric properties and relationship with teaching staff characteristics." Emotional and Behavioural Difficulties 23.2: 154-168. Ameli, A., Hasanah, U., Rahman, H., & Putra, A. M. (2020). Analisis keefektifan pembelajaran online di masa pandemi COVID-19. Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2(1), 28-37. Annisa, D. F., & Ifdil, I. (2016). Konsep Kecemasan (Anxiety) Pada Lanjut Usia (Lansia). Konselor, 5(2), 93-99. Aseta, P. (2021). Gambaran Faktor-Faktor Yang Mempengaruhi Kecemasan Mahasiswa Dalam Pembelajaran Daring Di Masa Pandemi Covid-19. Intan Husada: Jurnal Ilmiah Keperawatan, 9(2), 35-44. Baihaqi, M. G. (2014). Hubungan konsep diri dengan kecemasan siswa SMAN 1 Patianrowo dalam menghadapi ujian akhir nasional (Doctoral dissertation, Universitas Islam Negeri Maulana Malik Ibrahim). Christiansen, Ryan. (2021) "How the COVID-19 Pandemic Affected High School Student Mathematical Anxiety During Distance Learning". Demetriou, Loucia, Lydia Keramioti, and Demetris Hadjicharalambous. (2021). "Examining the Relationship between Distance Learning Processes and University Students’ Anxiety in Times of COVID-19." Demetriou, L., Hadjicharalambous, D., & L. keramiotiExamining The Relationship Between Distance Learning Processes And University Students Anxiety In Times Of Covid. European Journal of Social Sciences Studies 6.2 (2021): 123-141. Fajrina, Annisa. (2017) Perbedaan Tingkat Kecemasan Pada Ibu Primigravida Dengan Senam Hamil Dalam Menghadapi Persalinan Di Klinik Afiyah Dan Klinik Bhakti Pekanbaru. Diss. Poltekkes Kemenkes Riau. Fakhri, Abdul, Et Al. (2021). "Ritual Ibadah Sebagai Upaya Penurunan Kecemasan Pada Masa Pandemi Covid-19." Psisula: Prosiding Berkala Psikologi 2: 413-428. Fanhas F Kh, Elfan. (2021) “Kecemasan Orangtua Dan Bentuk Pengasuhan Anak Usia Dini Di Masa Pandemi Covid-19” Ghofur, A., Syarifuddin, M. A., Toyyibi, A. M., & Kurnianingsih, R. (2021). Strategi Lembaga Keuangan Syariah Menghadapi Pembiayaan Bermasalah Di Masa Pandemi Covid-19. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 11(2), 129–142. https://doi.org/10.47200/ULUMUDDIN.V11I2.795 Handayani, Oktarina Dwi. (2021). Persepsi Orangtua Terhadap Pelaksanaan Belajar Dari Rumah Pada Pendidikan Anak Usia Dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5.2: 1754-1763. Hapsari, Christianti Tri. (2021)."Distance learning in the time of Covid-19: Exploring students’ anxiety." ELT Forum: Journal of English Language Teaching. Vol. 10. No. 1. Hasmyati, S., & Arafah, A. A. (2018). Effective Learning Models In Physical Education Teaching. Deepublish. Hidayat, F., Hidayat, I., Ghofur, A., Setiawan Santoso, F., Universitas Negeri Malang, Fpp., Universitas Tribhuwana Tunggadewi, F., Kanjeng Sepuh Gresik, S., & Cokroaminoto Yogyakarta, U. (2021). Penanganan Kesehatan Pasien Reaktif COVID-19 Melalui Terapi Zikir Dan Lingkungan Wawasan Pengalaman Subyektif. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 11(1), 1–12. https://doi.org/10.47200/ULUMUDDIN.V11I1.424 Institut Pendidikan Indonesia Garut, (2020), Evaluasi Pembelajaran Jarak Jauh.https://institutpendidikan.ac.id/wpcontent/uploads/2020/07/Evaluasi-PJJ.pdf. Kholis, N. (2014). Paradigma Pendidikan Islam Dalam Undang-undang Sisdiknas 2003. Jurnal Kependidikan, 2(1), 71-85. King, Frederick B., (2001) Et Al. "Defining Distance Learning and Distance Education." AACE Journal 9.1. 1-14. Krismadika, A. P., & Fathoni, A. (2020). Implementasi Pembelajaran Jarak Jauh Selama Pandemi Covid-19 Di SD IT Al-Huda Wonogiri (Doctoral dissertation, Universitas Muhammadiyah Surakarta). Lase, Delipiter; Ndraha, Amurisi; Harefa, Gustav Gabriel. (2020). Persepsi Orangtua Siswa Sekolah Dasar Di Kota Gunungsitoli Terhadap Kebijakan Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19. Sundermann: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora Dan Kebudayaan, 13.2: 85-98. Ma’rifattullah, I. (2016). Hubungan Antara Kecerdasan Emosi dan Kepercayaan Diri Karyawan Terhadap Kecemasan Isu Pemutusan Hubungan Kerja (PHK) Pada Karyawan. Psikoborneo: Jurnal Ilmiah Psikologi, 4(3). Marliani, Novi, dan Arif Rahman Hakim. (2015)."Pengaruh Metode Belajar Dan Kecemasan Diri Terhadap Hasil Belajar Matematika Peserta Didik." JKPM (Jurnal Kajian Pendidikan Matematika) 1.1: 136-150. Mastoah, I., & MS, Z. (2020). Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 121–128. Moore, J. L., Dickson-Deane, C., & Galyen, K. (2011). E-Learning, Online Learning, And Distance Learning Environments: Are They The Same? The Internet and Higher Education, 14(2), 129–135. Doi:10.1016/J.Iheduc.2010.10.001 Nasional, Departemen Pendidikan. (2003)."Undang-Undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional." Jakarta: Depdiknas 33 Novikasari, I. (2017). Hubungan Antara Prestasi Belajar dan Tingkat Kecemasan Matematika pada Mahasiswa Calon Guru SD/MI. AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 5 (2), 120-127. Nugraha, F., & Hendrawan, B. (2019). Pengembangan Karakter Self Efficacy Pada Siswa Berkebutuhan Khusus Melalui Pembelajaran Self Regulated Learning. Early Childhood: Jurnal Pendidikan, 3(2), 40-45. Nurdyansyah, N. (2017). Sumber Daya dalam Teknologi Pendidikan. Universitas Muhammadiyah Sidoarjo. Nurhayati, R. (2020). Analisis SWOT Pelaksanaan Perkuliahan Daring Pada Masa Pandemi COVID-19 di STAI Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 63–72. https://doi.org/10.47200/JNAJPM.V5I1.916 Nuryanti, Evi N (2020). “Analisis Faktor-Faktor yang Mempengaruhi Prestasi Belajar Ekonomi berdasarkan Teori Sosial Kognitif Bandura”. Oktawirawan, Dwi Hardani. (2020). "Faktor Pemicu Kecemasan Siswa Dalam Melakukan Pembelajaran Daring Di Masa Pandemi Covid-19." Jurnal Ilmiah Universitas Batanghari Jambi 20.2: 541-544. O'Lawrence, H. (2006). The Influences of Distance Learning On Adult Learners. Techniques: Connecting Education and Careers, 81(5), 47-49. Pakpahan, R, & Fitriani Y (2020). Analisa Pemanfaatan Teknologi Informasi Dalam Pembelajaran Jarak Jauh Du Tengah Pandemic Virus Corona Covid-19. Journal of Information System Applied, Management, Accounting and Research 4 (2), 30-36. Pan, Feng, Et Al. (2020). "Time Course of Lung Changes On Chest CT during Recovery from 2019 Novel Coronavirus (COVID-19) Pneumonia." Radiology . Pandoman, A. (2020). Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC). Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 1–12. https://doi.org/10.47200/ulumuddin.v10i1.379 Pichette, François. (2009). "Second language anxiety and distance language learning." Foreign Language Annals 42.1: 77-93. Pramulasari, Ullima, (2018). Perbedaan Tingkat Kecemasan antara Mahasiswa Tahun Pertama dan Terakhir di Fakultas Kedokteran Universitas Muhammadiyah Semarang (Doctoral dissertation, UNIMUS) Santoso, F. S. (2020). Masa Depan Pendidikan Hukum Islam Di Perguruan Tinggi Keagamaan Islam Refleksi Pembelajaran Di Masa Kedaruratan Covid-19. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 13–26. Sari, Indah, Et Al. (2020). "Chemistry Learning via Distance Learning During the Covid-19 Pandemic." Tadris: Jurnal Keguruan Dan Ilmu Tarbiyah 5.1: 155-165. Setiawan, Adib Rifqi dan Arij Zulfi Mufassaroh. (2020) Lembar Kegiatan Siswa Untuk Pebelajaran Jarak Jauh Berdasarkan Literasi Saintifik Pada Topik Penyakit Coronavirus 2019 (COVID-19)”. Sherry, Lorraine. (1995) "Issues in Distance Learning." International Journal of Educational Telecommunications 1.4: 337-365. Sugiyono, (2012). Metode Penelitian Pendidikan (Pendekatan Kualitatif, Kuantitatif dan R&D). Bandung: Alfabeta Sukanto, D. (2020). Pembelajaran Jarak Jauh Dengan Media E-Learning Sebagai Solusi Pembelajaran Pada Masa Pandemi Corona Virus Disease 2019 (Covid-19). Syntax, 2(11), 835. Sulistyana, S. (2020). Pelaksanaan pembelajaran jarak jauh pada level pendidikan anak usia dini (Doctoral dissertation, Universitas Islam Negeri Maulana Malik Ibrahim). Surur, A. M., & Nadhirin, A. U. (2020). Manajemen Waktu Pembelajaran Daring Di Masa Pandemi Covid-19 Pada TK Dharma Wanita 1 Baleturi. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2). http://jurnal.uinbanten.ac.id/index.php/assibyan/article/view/2939 Susanti, M. A. (2019). Efektifitas Play Therapy Untuk Menurunkan Tingkat Sad (Saparation Anxiety Dysorder) Pada Anak Usia 5-7 Tahun (Studi Kasus Di TK Aisyiyah Bustanul Athfal Batusangkar). Syarifah, Rifatus. (2019). Identifikasi Respon Kecemasan Pada Pasien Pre Operasi Katarak Di Kabupaten Jember.Diss. Syarifuddin, M. (2020). Transformasi Gigital Persidangan di Era New Normal: melayani Pencari Keadilan di masa Pandemi Covid-19. Tirajoh, C. V., Munayang, H., & Kairupan, B. H. (2021). Dampak Pembelajaran Jarak Jauh Terhadap Kecemasan Orang Tua Murid di Masa Pandemi Covid-19. JURNAL BIOMEDIK: JBM, 13(1), 49-57. Ummah, Lulu Farhatul. (2020). "Integrasi Pendidikan Karakter Dalam Pembelajaran Jarak Jauh Bahasa Dan Sastra Indonesia." Jurnal Edukasi Khatulistiwa: Pembelajaran Bahasa Dan Sastra Indonesia 3.2 (2020): 85-93.Untuk Pembelajaran, Lembar Kegiatan Literasi Saintifik and Jarak Jauh, “Edukatif: Jurnal Ilmu Pendidikan”. Wahyuni, A. D., & Fajri, U. H. N. (2020). Implementasi E-Learning Sejarah Kebudayaan Islam Pada Masa Pandemi COVID-19 Di MTsN 4 Gunungkidul. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(2), 131–140. https://doi.org/10.47200/JNAJPM.V5I2.915 Wijayanti, Resti Mia; Fauziah, Puji Yanti. (2020). Perspektif Dan Peran Orangtua Dalam Program PJJ Masa Pandemi Covid-19 Di PAUD. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5.2: 1304-1312. Wilder-Smith, A., & Freedman, D. O. (2020). Isolation, quarantine, social distancing and community containment: pivotal role for old-style public health measures in the novel coronavirus (2019-nCoV) outbreak. Journal of travel medicine. Yanti, S., Erlamsyah, E,. Zikra, Z., dan Ardiz Z. (2013). Hubungan antara kecemasan dalam Belajar dengan Motivasi Belajar Siswa. Konselor, 2(1). Yaumi, M. (2015). Model Pengembangan Media Dan Teknologi Pembelajaran: Suatu Pengantar. Yazdi, M. (2012). E-learning sebagai media pembelajaran interaktif berbasis teknologi informasi. Jurnal ilmiah foristek, 2(1). Yulianingsih, W., Lestari, G. D., & Dewi, U. (2020). Learning Society Kampung Inggris. Yulinda, Y., Purwaningsih, D., & Sudarta, C. M. (2017). Latihan Yoga Dapat Menurunkan Tingkat Kecemasan pada Siklus Mentruasi Remaja Puteri. Jurnal Ners dan Kebidanan Indonesia, 5(1), 20-26.